O uso do cartão de crédito pelos gaúchos: há a influência do valor da marca e do materialismo no comportamento impulsivo de compra? - Rodrigues, Luis Adriano (2017)
This study aims to identify the factors that may influence impulse purchasing behavior among South Brazilian costumers with the credit card, observing demographic and socioeconomic factors. In addition, it seeks to verify if materialism and brand value impact on impulsive purchasing behavior and credit card use by that population. The survey method was adopted, and 384 structured questionnaires were applied face-to-face, observing the footwear field. The application of study was in Rio Grande do Sul – state of Brazil, contemplating its seven mesoregions. For the analysis of the data, we used confirmatory factorial analysis, descriptive statistics, ANOVA, Z test and Modeling of Structural Equations (MEE). In the results, it was possible to verify the agreement with studies from other authors in three hypotheses tested, being considered that only one of the hypotheses demonstrated not significant values. In general, South Brazilian costumers purchase impulsively; materialism impacts on impulsive purchases with credit card, and brand value did not have significant impact on impulse purchases in the context of this research.